1993
DOI: 10.1002/mds.870080208
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous apomorphine in parkinson's disease: Response to chronic administration for up to five years

Abstract: Subcutaneous apomorphine, administered by continuous waking-day infusion with boluses, or by repeated intermittent injection, was given to 71 parkinsonian patients with severe refractory levodopa related on-off fluctuations for 1-5 years. A mean reduction in daily off period time of approximately 50% was maintained, and the incidence of neuropsychiatric toxicity remained low on long-term follow-up. No clinically significant tolerance or loss of therapeutic effect was seen, although increasingly severe on-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
16

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(98 citation statements)
references
References 20 publications
7
75
0
16
Order By: Relevance
“…Double-blind clinical trials have shown the effectiveness of subcutaneously injected apomorphine in improving PD motor symptoms (Cotzias et al, 1970;Dewey et al, 2001). Despite these benefits, the longterm use of subcutaneous apomorphine infusions in the United Kingdom has been associated with significant technical difficulties and cutaneous adverse effects (Hughes et al, 1993). Because of these issues, infusions of apomorphine have not been very actively pursued in the United States.…”
Section: Dopamine Replacement Therapymentioning
confidence: 99%
“…Double-blind clinical trials have shown the effectiveness of subcutaneously injected apomorphine in improving PD motor symptoms (Cotzias et al, 1970;Dewey et al, 2001). Despite these benefits, the longterm use of subcutaneous apomorphine infusions in the United Kingdom has been associated with significant technical difficulties and cutaneous adverse effects (Hughes et al, 1993). Because of these issues, infusions of apomorphine have not been very actively pursued in the United States.…”
Section: Dopamine Replacement Therapymentioning
confidence: 99%
“…Subcutaneous apomorphine infusions have been used successfully in the United Kingdom for the treatment of motor fluctuations, but there have been significant technical difficulties and associated cutaneous adverse effects. 140 New delivery devices are being developed. Duodenal infusion of LD in a viscous gel (Duodopa) as monotherapy has been demonstrated to be safe, and has provided significant improvement over various oral combinations.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The general finding is that APO provides more time in motor states near normal performance and less time in 'off' and dyskinetic states as compared to conventional optimised therapy. Improvement in quality of life (QoL) may accompany the increased 'on' time, but so far publications on this aspect of APO infusion are sparse.…”
Section: Long-term Efficacy With Apomorphine Infusionmentioning
confidence: 99%